Comparison of RAPD-PCR and SDS-Page techniques to evaluate genetic variation among nine barley arieties (Hordeum spp.) - N.A., Tahir (Penerbit Universiti Kebangsaan Malaysia, 2014)
Genetic variability of barley (Hordeum spp) considered very important, reducing their genetic diversity affects negatively their tolerance to stress factors, causing the great loose of yield and implies the risk of their genetic vulnerability. Thus, the knowledge of genetic diversity of barly germplasm is important for breeding programmes and their conservation. Random amplified polymorphic DNA (RAPD) and SDS-PAGE techniques were used to examine the genetic variation among barley varieties. To maximize the genome coverage nine barley varieties from diverse origins were selected and analyzed with 18 selected RAPD markers. A total of 116 amplified bands and 63 polymorphic allelic variants were detected, ranging from 3 to 6 per locus with an average of 3.937. Genetic distance calculated from RAPD data ranged from 0.357 to 0.767. The dendrogram based on genetic distance estimation and PCA was produced two groupings that generally consistent with available genetic information. Zanbaka and Tadmor/roh6 were found to be closely related. Their genetic relationship was also confirmed by the facts that they shared a common ancestor and they were clustered together. A total of 14 unique bands (8 positives and 6 negatives) were identified out of 116 bands which could be considered for marker assisted selection. A slight range of variation in SDS-protein banding patterns was observed. A total number of 12 bands with different molecular weights were observed in SDS-PAGE, among these, only 5 bands were polymorphic. The dendrogram tree and PCA analysis showed that Elkheir and Canela were genetically distanced from the other genotypes. According to the results of RAPD and SDS-PAGE, a wide range of genetic diversity was observed among all varieties, indicating them as prime candidates of selective breeding for specific traits and broadening the genetic base.